Exchange rate dynamics, expectations, and monetary policy - Qianying Chen (Deutsche Bundesbank, 2011)
This paper re-investigates the implications of monetary policy rules on changes in exchange rate, in a risk-adjusted, uncovered interest parity model with unrestricted parameters, emphasizing the importance of modeling market expectations of monetary policy. I use consensus forecasts as a proxy for market expectations. The analysis on the Deutsche mark, Canadian dollar, Japanese yen, and the British pound relative to the U.S. dollar from 1979 to 2008 shows that, through the expectations of future monetary policy, Taylor rule fundamentals are able to forecast changes in the exchange rate, even over short-term horizons of less than two years. Furthermore, the market expectation formation processes of short-term interest rates change over time and differ across countries, which contributes to the time varying relationship between exchange rates and macroeconomic fundamentals, together with the time varying currency risk premia and exchange rate forecast errors.
Keywords: F31; E52; D83; C32; 330; Exchange Rate; Monetary Policy; Expectation; Learning; VAR; Consensus Forecast; Wechselkurs; Geldpolitik; Erwartungstheorie; Lernprozess; Schätzung; US-Dollar; Deutschland; Kanada; Japan; Großbritannien